Trade Openness and Productivity Growth in Emerging Markets: A Reevaluation of the Trade-Led Growth Hypothesis in Turkey Using the ARDL Framework - Bekun, Festus Victor; Yorucu, Vedat; Onwe, Joshua Chukwuma; Habib, Muhammad Danish; Yadav, Ashutosh; Demir, Ceren (Routledge Journals, Taylor & Francis Ltd, 2026)
This study examined the relationship between trade openness, foreign direct investment (FDI), and economic growth in Turkey, using the Trade-Led Growth (TLG) hypothesis framework. The analysis, via the ARDL model, confirmed that trade openness significantly boosts economic growth, supporting the TLG hypothesis. However, FDI's impact was more complex, with short-term challenges limiting its benefits. The study emphasized the importance of aligning FDI with national goals and stressed the need for domestic capital formation and labor market reforms. The findings highlight the necessity for inclusive strategies that build internal capacity while engaging in global trade.
Keywords: Economic growth; foreign direct investment; Trade-Led Growth Hypothesis; trade openness